Valuing coastal recreation and the visual intrusion from commercial activities in Arctic Norway - Aanesen, M; Falk-Andersson, J; Vondolia, GK; Borch, T; Navrud, S; Tinch, D (Ocean & Coastal Management, 2018)
The coastal zone in the Arctic is being extensively used for recreational activities. Simultaneously, there is an increasing pressure from commercial activities. We present results from a discrete choice experiment implemented in Arctic Norway, revealing how households in this region make trade-offs between recreational activities and commercial developments in the coastal zone. Our results show that, although people prefer stricter regulation of commercial activities, they welcome expansion in marine industries like aquaculture and marine fishing tourism. We also find evidence of high willingness-to-pay for new jobs; and this may partly explain the preferences for the commercial facilities in spite of the visual intrusion they create. On the other hand people expressed a clear dislike for littering of the beaches. Hence, the message to policy makers is to allow for commercial development in the coastal zone, but only under strict regulations, especially related to measures reducing the amount of marine debris.